2017
DOI: 10.1155/2017/3736201
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Human Papillomavirus 9-Valent Vaccine: A Meta-Analysis of Randomized Trials

Abstract: Vaccination against human papillomavirus (HPV) has been progressively implemented in most developed countries for approximately 10 years. In order to increase the protection of the vaccines, a 9-valent vaccine (HPV9) was developed, which provides protection against nine types of the virus. Studies evaluating its safety are rare. Thus, we performed a meta-analysis of three clinical trials assessing adverse effects on women randomly vaccinated with HPV9 or tetravalent vaccine (HPV4), with the objective of analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
(25 reference statements)
2
15
0
1
Order By: Relevance
“…Gardasil 9, by contrast, was associated with reports of predominantly mild adverse reactions mainly localized at the injection site. A similar result also emerged from a meta-analysis of randomized clinical trials of Costa et al, who showed that adverse reactions such pain and erythema occurred significantly more in the HPV9 group than in HPV4 [36].…”
Section: Vaccine Evaluationsupporting
confidence: 64%
“…Gardasil 9, by contrast, was associated with reports of predominantly mild adverse reactions mainly localized at the injection site. A similar result also emerged from a meta-analysis of randomized clinical trials of Costa et al, who showed that adverse reactions such pain and erythema occurred significantly more in the HPV9 group than in HPV4 [36].…”
Section: Vaccine Evaluationsupporting
confidence: 64%
“…In our earlier paper [1], we highlighted numerous studies attesting to HPV vaccine safety. Five years later, the safety profiles of the three HPV vaccines have been reviewed extensively, and the research continues to show they are safe, well tolerated, and have adverse effects similar to those experienced with other vaccines [12,13,113,114,115,116]. The most common adverse effects of the vaccines are soreness (pain), swelling, itching, and redness at the injection site, as well as syncope (fainting) [116].…”
Section: Safety and Communication About Safety Datamentioning
confidence: 99%
“…(iv) There are more and more reports demonstrating long-term vaccine effectiveness [7,8,9,10], including a recent study showing that HPV vaccine prevents invasive HPV-related cancers beyond cervical cancer [11]. (v) There is an accumulated body of evidence that HPV vaccines are very safe [12,13,14]. Despite continued empirical evidence of the vaccines' safety and effectiveness, and the broad backing of HPV vaccination from the medical and scientific communities, many countries continue to report that HPV vaccine uptake rates are low or have dropped steeply, often related to incorrect attributions of harm [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…HPV-induced cancers, including cervical cancer and oropharyngeal cancer, are responsible for over 300,000 deaths annually worldwide ( 2 ), making HPV infection a major public health problem. Several HPV vaccines have been shown to safely and effectively prevent infection by cancer-causing HPV types, thus preventing the antecedent growths that inevitably lead to cervical cancer ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%